Cross-sectional fat fraction analysis of the gluteus medius and minimus muscle in asymptomatic vs. symptomatic hips using 2-point Dixon MRI - Georg Wilhelm Kajdi; Sophia Samira Goller; Patrick Oliver Zingg; Reto Sutter (BMC Musculoskeletal Disorders)
Abstract Background To evaluate cross-sectional fat fractions (FF) of the hip abductors in asymptomatic compared to symptomatic hips in elderly patients using 2-point Dixon MRI, and compare them to the Goutallier classification. Methods In this retrospective (clinicial trial number: not applicable) single-center study, two radiologists assessed cross-sectional fatty infiltration of the gluteus minimus (Gmin) and medius (Gmed) muscles in both hips of patients with unilateral greater trochanteric pain syndrome (GTPS) using 2-point Dixon MRI-derived fat fractions (FF). Additionally, fatty infiltration was assessed on T1w sequences using the Goutallier classification. Differences in fatty infiltration for both methods between the symptomatic and asymptomatic hips were assessed using the Wilcoxon signed-rank test. Results 42 patients (mean age 65.1 ± 13.7 years, 28 females) were analyzed. Median FF in asymptomatic hips was 13.5 ± 15.2% for the Gmin and 14.2 ± 11.6% for the Gmed muscle (vs. 13.9.±14.1% and 16.2 ± 18.4% on the symptomatic side). FF of Gmed were significantly lower on the asymptomatic side than on the symptomatic side (p ≤ .043). No significant difference was observed neither for FF of the Gmin muscle (p ≥.30) nor for the Goutallier gradings of the Gmin (p ≥ .06) and Gmed (p ≥ .13) muscle between the asymptomatic vs. symptomatic sides. Conclusion Median FF were close to 14% for Gmin and Gmed in elderly asymptomatic hips, with a tendency for lower fat fractions in males. Significantly higher fat content of the Gmed was present in symptomatic hips, which was solely detectable by FF analysis and not by Goutallier grading. Reproducibility of FF analysis surpassed the Goutallier assessment.